2017
DOI: 10.3934/publichealth.2017.2.149
|View full text |Cite
|
Sign up to set email alerts
|

Racial Differences in Neighborhood Perceptions and their Influences on Physical Activity among Urban Older Women

Abstract: BackgroundProper levels of physical activity (PA) are important to healthy aging. Little is known about racial differences in influences of neighborhood perceptions (NP) on PA and use of neighborhood resources among community-dwelling older women.Materials and methodsIn 2014 and 2015, 49 white and 44 black women of age 65 and older living in Washington, DC were queried about their PA, NP, use of neighborhood resources and sociodemographic characteristics. They wore an accelerometer and a Global Positioning Sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 45 publications
1
6
0
Order By: Relevance
“…Older Black adults with above median PNSCS walk less than those with below PNSCS. This finding is similar to the results from Li et al (2017) where neighborhood perceptions were not associated with higher frequencies of moderate-to-high intensity activities and exercise activities among Black urban women (W. Li et al, 2017).…”
Section: Discussionsupporting
confidence: 88%
“…Older Black adults with above median PNSCS walk less than those with below PNSCS. This finding is similar to the results from Li et al (2017) where neighborhood perceptions were not associated with higher frequencies of moderate-to-high intensity activities and exercise activities among Black urban women (W. Li et al, 2017).…”
Section: Discussionsupporting
confidence: 88%
“…Of the 102 interactions assessed, 12 were found to be significant. More specifically, seven significant interactions were found for the effect of education level on leisure-time walking [73,77], leisure-time walking within the neighbourhood [73], and leisure-time walking and cycling combined [60]; three were found for race/ethnicity on overall LTPA [45] and leisure-time walking within the neighbourhood [118]; and two for employment status on LTPA other than walking [43]. Overall, the direction of effects was inconclusive.…”
Section: Socio-demographic Moderatorsmentioning
confidence: 96%
“…Other socio-demographic factors, such as level of education, income, employment status, race/ethnicity and marital status, have been investigated as moderators of environmental correlates of all LTPA outcomes except leisure-time cycling [43,45,60,73,77,82,93,100,118]. Of the 102 interactions assessed, 12 were found to be significant.…”
Section: Socio-demographic Moderatorsmentioning
confidence: 99%
“…Research on perceived neighborhood characteristics also shows differences by race. Some research has shown that White respondents perceive more neighborhood disorder than Black respondents [53], yet research on older women has shown that older, Black women had significantly lower perceptions of safety compared with White women [54]. One cross-sectional study that examined the effect of perceived neighborhood safety on volunteerism stratified by race found that perceived neighborhood safety was only a significant determinant of volunteerism among White respondents and was not significant among non-Hispanic Asian, non-Hispanic Black, or Hispanic adults over the age of 50 years [20].…”
Section: Gender and Race Differences In Perceived Safety And Volunteerismmentioning
confidence: 99%